Qualitative and Quantitative analysis of Lycium barbarum L. Flavonoids from leaves - Zainab Y. Mohammed; Khulood W.Alsamarrae (College of Pharmacy University of Baghdad, 2017)
There is no phytochemical study about Iraqi wild type Lycium barbarum  L. and its active components. However ;L.barbarum as a traditional Chinese herb possessing vital biological activities , such as prevention of cancer and age-related macular degeneration, is widely used in Asian countries. The main active components of this plant have been identified as flavonoids, carotenoids especially zeaxanthin and polysaccharides, all of these components have been reported to be closely associated with the health-enhancing effect. In this study a method for investigating flavonoids from the leaves of wild type L. barbarum that are grown naturally in Iraqi deserts and then estimate the total quantity of these flavonoids as Quercetin. For qualitative assay   classical chromatographic methods was applied; preparative thin layer chromatography (PTLC). The application employed different solvent systems for flavonoids separation. The best mobile phase   for extracting and separation different flavonoids from L. barbarum leaves was chosen for (PTLC) in corresponding with standards to investigate each separated flavonoid   for this methods. Total Flavonoids from leaves extract were calculated as Quercetin flavonoid represented the quantitative assay in this study. Results showed that the plant is rich with different flavonoids among them (rutin, quercetin, kaempferol, luteolin) and others. The technique with best solvent system for flavonoids separation is by preparative TLC chromatography with (Chloroform: Glacial acetic acid: Formic acid) in the ratio of (44:3.5:2.5). Iraqi wild type Lycium barbarum contain about  (11.28 mg /g dried leaves ) total flavonoids as quercetin. Keywords: Lycium barbarum Flavonoids, Flavonoids TLC, PTLC, Quercetin, Kaempferol, Luteolin, Rutin.